Distal radial access in the right anatomical snuffbox for coronary angiography and interventions: a prospective observational study. (14th October 2021) - Chatterjee, K; Sahu, A; Khanna, R; Kumar, S; Tewari, S; Kapoor, A; Goel, P K; Garg, N; ,
Abstract: Background: Distal radial access in the anatomical snuffbox is a novel technique for vascular access. However, limited clinical data is available, mainly limited to the left distal radial access. In view of the paucity of data on right distal radial access; this study was conducted to assess the feasibility, efficacy and safety of the right distal radial approach as a default access route for transradial catheterization. Methods: We enrolled 159 consecutive patients with a palpable right distal radial pulse prospectively at a single center. A detailed clinical evaluation, laboratory tests and echocardiographic examination was done. Doppler examination of distal radial artery for its patency and size was done before puncture attempt. The right distal radial artery was punctured using the back wall technique. Primary outcome was successful puncture of distal right radial artery. Secondary outcomes were number of puncture attempts, pain score, radial artery spasm, forearm and distal radial hematoma, proximal and distal radial artery occlusion, bleeding and other vascular complications, access site crossover due to distal radial access failure, contrast volume used, and radiation dose. Results: Distal radial puncture was successful in 144/159 (90.1%) patients. The mean distal radial artery diameter was 2.2±0.25 mm. Mean pain score by visual analogue scale was 2.36±1.9. There were no bleeding events. Snuffbox hematoma was seen in 11 (7.6%) patients and forearm hematoma occurred in 5 (3.5%) patients. There were 9 (6.3%) cases of radial spasm, 4 (2.8%) cases of radial occlusion at distal access site and 1 (0.7%) forearm radial artery occlusion. Conclusions: The right distal radial access is a feasible, safe and efficacious alternative approach for coronary angiogram and interventions. FUNDunding Acknowledgement: Type of funding sources: None.